Controversy Over Liver Transplantation or Resection for Neuroendocrine Liver Metastasis: Tumor Biology Cuts the Deal. Issue 5 (17th May 2023) - Eshmuminov, Dilmurodjon; Studer, Debora J.; Lopez Lopez, Victor; Schneider, Marcel A.; Lerut, Jan; Lo, Mary; Sher, Linda; Musholt, Thomas J.; Lozan, Oana; Bouzakri, Nabila; Sposito, Carlo; Miceli, Rosalba; et al.
Abstract : Background: In patients with neuroendocrine liver metastasis (NELM), liver transplantation (LT) is an alternative to liver resection (LR), although the choice of therapy remains controversial. In this multicenter study, we aim to provide novel insight in this dispute. Methods: Following a systematic literature search, 15 large international centers were contacted to provide comprehensive data on their patients after LR or LT for NELM. Survival analyses were performed with the Kaplan-Meier method, while multivariable Cox regression served to identify factors influencing survival after either transplantation or resection. Inverse probability weighting and propensity score matching was used for analyses with balanced and equalized baseline characteristics. Results: Overall, 455 patients were analyzed, including 230 after LR and 225 after LT, with a median follow-up of 97 months [95% confidence interval (CI): 85–110 months]. Multivariable analysis revealed G3 grading as a negative prognostic factor for LR [hazard ratio (HR)=2.22, 95% CI: 1.04–4.77, P =0.040], while G2 grading (HR=2.52, 95% CI: 1.15–5.52, P =0.021) and LT outside Milan criteria (HR=2.40, 95% CI: 1.16–4.92, P =0.018) were negative prognostic factors in transplanted patients. Inverse probability-weighted multivariate analyses revealed a distinct survival benefit after LT. Matched patients presented a median overall survival (OS) of 197 months (95% CI: 143–not reached) and a 73% 5-year OS after LT, and 119 months (95% CI: 74–133 months) and a 52.8% 5-year OS after LR (HR=0.59, 95% CI: 0.3–0.9, P =0.022). However, the survival benefit after LT was lost if patients were transplanted outside Milan criteria. Conclusions: This multicentric study in patients with NELM demonstrates a survival benefit of LT over LR. This benefit depends on adherence to selection criteria, in particular low-grade tumor biology and Milan criteria, and must be balanced against potential risks of LT.